DNA Sequence Analysis of dtxR Gene (Partial) of Corynebacterium diphtheriae Causing Diphtheria in Jawa and Kalimantan Islands, Indonesia - Sunarno Sunarno; Yuanita Mulyastuti; Nelly Puspandari; Kambang Sariadji (The Indonesian Biomedical Journal, 2017)
BACKGROUND: dtxR gene is a global regulator that can be used as a marker for detection of Corynebacterium diphtheriae (C. diphtheriae) and it is also a representative tool for mapping purpose (molecular typing) of this bacteria. The aim of this study was to analyze the DNA sequences of partial dtxR gene of C. diphtheriae causing diphtheria in some region of Indonesia. DNA sequence analysis was used to verify the accuracy of the in-house multiplex polymerase chain reaction (PCR) method that used for detection of C. diphtheriae in the clinical specimen as well as a preliminary study to determine the strain diversity of C. diphtheriae circulating in Indonesia.METHODS:Ten PCR products targeting the dtxR gene that have been detected as positive C. diphtheriae previously by in-house multiplex PCR used as samples in this study. The DNA sequencing carried out by Sanger method and the sequence data was analyzed by Bioedit software offline and basic local alignment sequence typing (BLAST) online.RESULTS: All of DNA sequence analyzed in this study were similar or identical to the dtxR gene sequence data of C. diphtheriae registered in GenBank. Within the 162 nucleotides (base 150-311) of dtxR gene that analyzed, at least 2 clonals were found among 10 samples. Substitutions of 2 nucleotides (base 225 and 273) was detected, both were silent mutation.CONCLUSION:Ten partial DNA sequences of dtxR genes in this study verify the accuracy of in-house multiplex PCR which used to identify the bacteria causing diphtheria in the clinical specimen. The DNA sequences also represent the existing diversity of the bacteria causing diphtheria circulating in Indonesia.KEYWORDS: dtxR, C. diphtheriae, diphtheria, Indonesia